(untitled) (Research, Society and Development, 2021)
Vaccine protocols were established for dogs and cats, considering the circulating period of maternal antibodies from the puppies, the type of antigen used to make the vaccines and the vaccine immunity duration. This study aimed to approach the duration of vaccine immunity against the canine parvovirus (CPV-2) and the canine distemper virus (CDV), as determining factor to choose the adequate vaccine protocol, besides to stand out the main implications found in Brazil that difficult the application of these current protocols, as the technical challenges to use them. For that, this article described some information about the types of current vaccines, the immunity duration against the CPV-2 and CDV, as well the respective vaccine protocols that were applied. The searches were done in the database of PubMed, SciELO, Google Scholar, Capes Journals and academic books, by the following keywords: vaccination guidelines; humoral immune response; vaccination strategy; distemper; parvovirus infection; and duration of vaccine immunity. Considering the facts, it is understood that the annual revaccination against the CPV-2 and CDV for dogs must be individually assessed, because the vaccine immunity has an average duration of three years, that is, the best alternative for the animal would be the application of routine serological tests, aiming to assess if the antibodies titration remains protective. Another alternative is the use of divalent or trivalent vaccines.